German New Onset Diabetes in the Young Incident Cohort Study: DiMelli Study Design and First-Year Results (The Review of Diabetic Studies, 2023)
BACKGROUND: Diabetes incidence in childhood and youth is increasing worldwide, including autoimmune and non-autoimmune cases. Recent findings suggest that there is a larger than expected proportion of type 2 diabetes in youth, and potential cases of intermediate diabetes phenotypes. Most pediatric diabetes registries focus on type 1 diabetes. Also, there is an absence of reliable data on type 2 diabetes incidence in youth. AIMS: The DiMelli study aims to establish a diabetes incidence cohort registry of patients in Germany, diagnosed with diabetes mellitus before age 20 years. It will be used to characterize diabetes phenotypes by immunologic, metabolic, and genetic markers. DiMelli will assess the contribution of obesity and socio-demographic factors to the development of diabetes in childhood and youth. METHODS: Recruitment of patients started in 2009, and is expected to continue at a rate of 250 patients per year. RESULTS: 84% of the 216 patients recruited within the first year were positive for multiple islet autoantibodies, 12% for one islet autoantibody, and 4% were islet autoantibodynegative. Patients with multiple islet autoantibodies were younger and had lower fasting C-peptide levels, compared to islet autoantibody-negative patients (median age 10.0 vs. 14.1 years, p < 0.01). CONCLUSIONS: Results from the first year of the study show that DiMelli will help to reveal new knowledge on the etiology of diabetes, and the contribution of genetic predisposition and environmental risk factors to the different types of diabetes.